The mystery of abdominal snow-grip sensation: emphysematous cystitis complicated with bladder gangrene and rupture—case report and literature review - Zhou, Yiwen; Cai, Yuxi; Yang, Yi; Xu, Chenyang; Xiang, Jianbin; Fang, Zujun; Mao, Shanhua (Frontiers in Medicine, 2024)
Emphysematous cystitis (EC) refers to a rare form of complicated urinary tract infection (UTI), which is typically observed in elderly females with severe diabetes mellitus. EC was triggered by bacteria, producing gas filled cysts in the bladder wall and lumen, the most common of which are Escherichia coli and Klebsiella pneumoniae.Since EC could be potentially life-threatening, severe form of EC (like septic shock) can cause gangrenous cystitis (GC). This case report describes an 85-year-old female patient with type 2 diabetes mellitus (DM) who presented with EC and bladder gangrene due to the growth of Candida glabrata in urine. Our case describes patient's progression in detail, ranging from the initial clinical manifestations to specific management actions, which may provide new insights and ideas for the diagnosis and treatment of such disease.